1988
DOI: 10.1172/jci113747
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of pleural effusions to increased permeability pulmonary edema in anesthetized sheep.

Abstract: We studied anesthetized sheep to determine the relationship between increased permeability pulmonary edema and the development and mechanism of pleural effusion formation. In 12 sheep with intact, closed thoraces, we studied the time course of pleural liquid formation after 0.12 ml/kg i.v. oleic acid. After 1 h, there were no pleural effusions, even though extravascular lung water increased 50% to 6.0±0.7 g/g dry lung. By 3 h pleural effusions had formed, they reached a maximum at 5 h (48.5±16.9 ml/thorax), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 14 publications
1
30
0
1
Order By: Relevance
“…However, in the 1980s, a combination of in vivo and in vitro studies demonstrated that the primary mechanism driving the resolution of alveolar edema was vectorial transport of sodium into the interstitial space, thereby creating an osmotic gradient for absorption of water from the distal airspaces of the lung (7). Several investigators demonstrated that the excess interstitial fluid was cleared by lung lymphatics, and by bulk flow across the low-resistance visceral pleura into the pleural space (1,8). A negative interstitial pressure gradient, even under conditions of edema, was shown to be the major force for the removal of interstitial edema fluid into lung lymphatics and the mediastinum (9).…”
Section: Alveolar Edema Fluid Clearance In the Uninjured Lungmentioning
confidence: 99%
“…However, in the 1980s, a combination of in vivo and in vitro studies demonstrated that the primary mechanism driving the resolution of alveolar edema was vectorial transport of sodium into the interstitial space, thereby creating an osmotic gradient for absorption of water from the distal airspaces of the lung (7). Several investigators demonstrated that the excess interstitial fluid was cleared by lung lymphatics, and by bulk flow across the low-resistance visceral pleura into the pleural space (1,8). A negative interstitial pressure gradient, even under conditions of edema, was shown to be the major force for the removal of interstitial edema fluid into lung lymphatics and the mediastinum (9).…”
Section: Alveolar Edema Fluid Clearance In the Uninjured Lungmentioning
confidence: 99%
“…These have not been supported by data. Our understanding progressed when several investigators, working both in vivo and in vitro, demonstrated that excess interstitial fluid was cleared by a combination of lung lymphatics and bulk flow across the visceral pleura to the pleural space [113], driven by active transport of sodium into the interstitial space [114]. This is driven by Na/K-ATPase situated at the basolateral surface of the epithelial cell, generating a gradient to facilitate sodium entry at apical cell surface sodium channels.…”
Section: Pathogenesis Of Ardsmentioning
confidence: 99%
“…They originate as a proteinaceous plasma exudate that accumulates in the lung interstitium and traverses the visceral pleura to enter the pleural space [22,23]. This study found that zymosan priming prevented the development of pleural effusions in hyperoxic rats (Table 1, ZP group).…”
Section: Zymosan Priming Prevents Pleural Effusions In Hyperoxic Ratsmentioning
confidence: 58%